2001
DOI: 10.1192/bjp.178.40.s53
|View full text |Cite
|
Sign up to set email alerts
|

Early-onset Alzheimer's disease in Scotland: environmental and familial factors

Abstract: BackgroundAlzheimer's disease (AD) is a common, complex, age-related disorder in which both genetic and environmental factors are important.AimsTo integrate recent studies on genetic and environmental factors in AD into a multi-factorial disease model.MethodDisease models to explain gene-environment interaction in cardiovascular disease are related to observations on AD.ResultsInformative, community-based studies on the genetic epidemiology of AD are rare. Putative risk factors from the Scottish studies includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 77 publications
(74 reference statements)
0
14
0
Order By: Relevance
“…First, subjects in the category of manual work involving goods production in our population included workers such as tailors and dressmakers, house constructers and related workers, furniture makers and carpenters, mechanical technicians, formers, typographers, welders, and metal workers. These individuals, especially those that were involved in goods production, could be exposed to multi-toxics in the work environment [Cohen, 1994;Whalley, 2001]. Studies have suggested that exposure to neurotoxic materials (e.g., heavy metals, solvents, pesticides, or defoliants) and electromagnetic fields may lead to global lesions of several neurological diseases, including Alzheimer's disease and other dementias [Kukull et al, 1995;Sobel et al, 1996;Hébert et al, 2000;Tyas et al, 2001].…”
Section: Discussionmentioning
confidence: 99%
“…First, subjects in the category of manual work involving goods production in our population included workers such as tailors and dressmakers, house constructers and related workers, furniture makers and carpenters, mechanical technicians, formers, typographers, welders, and metal workers. These individuals, especially those that were involved in goods production, could be exposed to multi-toxics in the work environment [Cohen, 1994;Whalley, 2001]. Studies have suggested that exposure to neurotoxic materials (e.g., heavy metals, solvents, pesticides, or defoliants) and electromagnetic fields may lead to global lesions of several neurological diseases, including Alzheimer's disease and other dementias [Kukull et al, 1995;Sobel et al, 1996;Hébert et al, 2000;Tyas et al, 2001].…”
Section: Discussionmentioning
confidence: 99%
“…We could not control for interactions between advanced paternal age and environmental factors that might have influenced the BPI onset in probands. Interaction between older paternal age and exposure of the fathers to toxic chemicals having influence on the disease AO in men was described by Whalley [2001] in Alzheimer's disease in offspring of Scottish coal miners. Similarly, exposure of the probands to long‐lasting psychosocial stressors may trigger an earlier AO through depressive episodes.…”
Section: Discussionmentioning
confidence: 99%
“…In Alzheimer's disease, the research has focussed on the relationship between the age‐of‐onset (AO) of the disorder and the parental age at the child's birth. A Scottish study [Whalley, 2001] found a sex‐specific effect consisting of a negative correlation between paternal age and AO of the disease only in men. There was no correlation between paternal age and Alzheimer's AO in women.…”
Section: Introductionmentioning
confidence: 99%
“…A modifier variant can enhance or suppress the phenotype of a monogenic disorder as well as alter the onset, severity, or progression of the phenotype (1)(2)(3)(4)(5). The site of action of modifiers can be at any point from transcription to posttranslational modification of the target genes.…”
Section: Introductionmentioning
confidence: 99%